Efektivitas Logoterapi untuk Meningkatkan Self-Esteem dan Kebermaknaan Hidup Penderita Skizofrenia - Luke Setyo Anggoro (LPPM Universitas Abdurrab, 2025)
The aim of this research is to determine the effectiveness of logotherapy to increase the level of self-esteem and increase the meaning of life in individuals who experience residual schizophrenic disorder. The pre-experimental one group pretest-posttest method was used as the research design. The sampling technique uses purposive sampling. A total of 6 people with an age range of 21-50 years were used as research participants, this was due to the limited population that met the inclusion criteria and the logotherapy approach which is in-depth and requires intensive involvement in each therapy session. The instruments used are the Indonesian version of the RSES for self-esteem and the Indonesian version of the MLQ to measure the meaning of life, these measuring instruments have been tested for validity and reliability. The therapy technique uses existential analysis from logotherapy. Data analysis technique using paired sample t test. The research results showed that there was a significant difference in self-esteem. This is based on the t test with a p value which obtained a value of 0.000 <0.005. Then there is also a significant difference in the meaning of life, as proven by the t test analysis with a p value which obtained a value of 0.000 <0.005. According to statistical data analysis, it can be concluded that logotherapy using existential analysis techniques can increase the level of self-esteem and increase the meaning of life in individuals who experience residual schizophrenic disorders. These findings can be the basis for the development of broader psychological therapy programs in the rehabilitation of schizophrenia sufferers, especially in improving their quality of life.